The first record of Euphorbia hypericifolia L. (Euphorbiaceae) in Libya - Hadi Mahklouf, Mohammed (Biodiversity: Research and Conservation, 2023)
The herb Euphorbia hypericifolia L. was recorded for the first time in the flora of Libya. The species was collected in Tobruk city in north-eastern Libya in 2022. It is presented here with updated nomenclature, taxonomic description, geographical distribution, and the place of occurrence in Libya. A coloured photograph taken in the field is also provided. The voucher specimens have been deposited in the Herbarium of Botany Department (ULT), Faculty of Sciences, University of Tripoli, Libya.